Design and microstructure analysis of globules in Al-Co-La-Pb immiscible alloys with an amorphous phase. (5th March 2017) - Nagase, Takeshi; Takemura, Mamoru; Matsumuro, Mitsuaki; Matsumoto, Megumi; Fujii, Yoshikazu
Abstract: An immiscible alloy with an amorphous phase, Al-Co-La-Pb, was designed by the combination of empirical rules, prediction of phase diagrams based on ab initio calculations, and thermodynamic calculations. The solidification microstructure of rapidly solidified Al-Co-La-Pb melt-spun ribbons was investigated. Liquid-phase separation and the formation of an amorphous phase occurred simultaneously in the Al-Co-La-Pb alloy, resulting in the formation of Pb globules embedded in the Al-Co-La–based amorphous matrix. The particle size distribution of the globules and the formation of Pb nanoglobules were explained by the multistep liquid-phase separation. STEM observation clarified the microstructure of oxygen-enriched globules with double shell layers in the Al-Co-La-Pb alloy. Graphical abstract: Highlights: An immiscible Al-Co-La-Pb alloy with an amorphous phase was designed. Ultra-fine Pb globules, dispersed in Al-based amorphous alloys, were successfully obtained. Multistep liquid-phase separation occurred in Al-Pb–based immiscible alloys. STEM clarified the particle structures in Pb-enriched and oxide globules